2022
DOI: 10.1103/physrevfluids.7.084304
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of dry and immersed polydisperse granular columns: A unified runout description

Abstract: The granular column collapse is a simplified version of granular flows such as landslides, avalanches, and other industrial processes mobilized in air or within a fluid. In this configuration, the particles collapse in an accelerating phase, reaching a state of constant spreading velocity until they decelerate and stop. Granular flows commonly involve particles of different sizes, a property termed polydispersity. Understanding the role of polydispersity remains a challenging task that is often analyzed with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 40 publications
3
22
0
Order By: Relevance
“…The latter result, in the granular column configuration, is in agreement with previous studies that have shown the independence of the shear strength of polydisperse granular materials when they reach a residual stage at large deformation (Nguyen et al 2015;Cantor et al 2018;Cantor, Azéma & Preechawuttipong 2020;Polanía et al 2023). The effect of polydispersity on immersed granular flows has been studied less, but it has been shown with a numerical approach that the collapse of immersed columns is delayed with an increase in the polydispersity level (Polanía et al 2022). Despite these previous works, the effect that polydispersity has on immersed granular columns remains insufficiently investigated, especially experimentally.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…The latter result, in the granular column configuration, is in agreement with previous studies that have shown the independence of the shear strength of polydisperse granular materials when they reach a residual stage at large deformation (Nguyen et al 2015;Cantor et al 2018;Cantor, Azéma & Preechawuttipong 2020;Polanía et al 2023). The effect of polydispersity on immersed granular flows has been studied less, but it has been shown with a numerical approach that the collapse of immersed columns is delayed with an increase in the polydispersity level (Polanía et al 2022). Despite these previous works, the effect that polydispersity has on immersed granular columns remains insufficiently investigated, especially experimentally.…”
Section: Introductionsupporting
confidence: 90%
“…High packing fractions, due to high polydispersity levels, frustrate the rapid percolation of water into the granular structure and produce a retrogressive collapse mechanism. Similar collapse mechanisms have been observed for sand columns (Thompson & Huppert 2007) and polydisperse columns in two-dimensional simulations (Polanía et al 2022). The motion of monodisperse collapses finishes earlier than that of polydisperse collapses, resulting in longer runout distances for systems with λ = 20 than for λ = 1.…”
Section: Collapse Sequencesupporting
confidence: 74%
See 2 more Smart Citations
“…The first part of this section consists of reproducing the granular collapses of Rondon et al (2011). Although, a broad number of works (Izard et al, 2018; Jing, Yang, Kwok, & Sobral, 2019; Meng, Liao, Yu, Li, & An, 2021; Polanía, Cabrera, Renouf, & Azéma, 2022; Riffard & Ris, 2022; Sun, Zhang, Wang, & Liu, 2020; Wang et al, 2017a) have predicted the main features of granular column collapses immersed in a viscous fluid, only a few (Wang, Wang, Peng, & Meng, 2017b; Yang, Jing, Kwok, & Sobral, 2020) have successfully captured the dynamics of Rondon's experiments for both initially loose and dense granular columns, and even fewer have done it with a continuum approach (Baumgarten & Kamrin, 2019; Bouchut et al, 2017; Lee, 2021; Phan, Bui, & Nguyen, 2022; Rauter, 2021; Shi et al, 2021; Si, Shi, & Yu, 2018). The dilatancy model presented herein was able to capture the pore pressure feedback in one-dimensional and 2-D granular avalanches (Montellà et al, 2021) with reasonably good agreement.…”
Section: Resultsmentioning
confidence: 99%